A Bibliometric Analysis of Research on Social Studies Education in Primary Schools: Performance Analysis and Scientific Mapping - Baihaqi Siddik Lubis; Melyani Sari Sitepu; Nur Fadillah; Mai Sri Lena (Journal of Innovation in Educational and Cultural Research, 2026)
Social studies education offers an integrated discipline that addresses societal issues, especially in elementary school. This subject has attracted considerable attention from the academic world as a reformed educational paradigm that has frequently been neglected. Nevertheless, there is a dearth of literature that integrates findings from prior studies. This study aims to examine the present condition of social studies education research in elementary schools. The researcher utilizes bibliometric analysis to investigate literature from the Scopus database using targeted keyword phrases. This study examines 235 out of 563 eligible papers that were subjected to screening. Instruments like Biblioshiny and VOSviewer are employed to assess metrics like productivity, impact, cooperation, and knowledge. Notwithstanding variations in citation rates, the results demonstrate an increasing interest in research regarding social studies teaching. The United States serves as the principal regional center for global networking, with significant contributions from Turkey and Indonesia as well. The examination of contemporary subjects and clusters offers possible theoretical frameworks and underscores upcoming research tendencies. This study provides significant insights and recommendations for future research to enhance social studies curriculum in primary schools.